Analisis Perbandingan Performansi Kontroler Floodlight, Maestro, RYU, POX dan ONOS dalam Arsitektur Software Defined Network (SDN) - Moh Wahyudi Putra; Eko Sakti Pramukantoro; Widhy Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The main network infrastructure that is almost entirely managed by vendor leads to the increasing complexity of network built, so it is needed an approach to manage and implement the network to support the diverse needs, that is the needs of using Software defined network (SDN). Software defined network (SDN) has a basic concept of separating the control plane and data plane, so the network can be programmed individually from the data center. Some of the existing controllers are Maestro, Floodlight, RYU, POX and ONOS. To know which controller has the best performance, then doing a performance comparison analysis among the controllers. Tests conducted in this research is using mininet as an emulator to design test topology and Cbench to evaluate parameters of throughput and latency. Based on the test, we found that Maestro controller has better capability to handle data flow with larger amount of data compared to Floodlight controller, RYU controller, POX controller, or ONOS controller. Thus, the Maestro controller has a better chance to guarantee the processing of large amounts of data. With the difference of throughtput value in the range of 500 to 4000 flow/s. With Maestro controller, we also got better and superior latency values with the difference range of around 1000 ms up to 5000 ms.